Megatrends and their use in economic analyses of contemporary challenges in the world economy - Malik, Radosław; Janowska, Anna Anetta (Megatrendy i ich wykorzystanie w ekonomicznych analizach współczesnych wyzwań w gospodarce światowej, 2018)
The objective of the article was to perform a literature review to analyze the use of megatrends as an analytical framework in various areas of economic and social discourse. Following SALSA methodology, the scope of the research covers peer reviewed articles published between 2010 and 2018. The results show that the concept of megatrends has been utilized in analyzing the impact of fundamental economic and social changes in three main areas: foresight studies of selected industries, analyses of existing and anticipated changes in management and business practices, and other socio-economic topics. The content of the most frequently used megatrends covered: technology developments, environmental changes, demographic shifts, urbanization, and changes in geopolitics. The most coherently defined megatrends that are frequently envisaged to exercise influence on the contemporary world, and are expected to continue to do so in the future, are: digitization and development of ICT and related technologies, urbanization growth, scarcity of resources and climate changes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 209-220
Keywords: megatrends; megatrends analyses; foresight; literature review; economic analysis; world economy; analiza megatrendów; przegląd literatury; analiza ekonomiczna; gospodarka światowa; studia nad przyszłością